Thule Period Archaeology at the Pembroke Site, Cambridge Bay - Max Friesen; Max Friesen (Polar Data Catalogue, 2013)
The Pembroke Site is the earliest Thule site known from the Cambridge Bay area, and is located on a knoll next to Freshwater Creek, which is a major char river. The site contains five small winter houses, and five warm season structures which are visible as high-walled, well-built tent outlines. Above these ten dwellings, on top of the knoll, is a large "karigi", a communal structure which is much larger than any other feature. Pembroke was investigated in the 1960s by William Taylor, Jr. His investigation of five of the site's structures yielded important information, however new research was required in order to recreate early Inuit lifeways in the area in more detail. During the 2008 IPY field season, we excavated two winter houses, both of which were built of boulders with floors made out of flat flagstones. One of them was occupied for a very brief time, based on the fact that it contained very few artifacts and animal bones. The second house had two separate floors, so was probably occupied for at least two years. We also excavated one tent ring which contained a very dense concentration of artifacts, probably representing a fall occupation. Finally, we excavated the karigi, which exhibited a well-made stone bench around its perimeter. Overall, the site appears to represent a brief stay by a Thule group which was probably in transit, likely moving from Alaska to eastern or central Nunavut.